Perancangan Sistem Informasi Manajemen Keuangan Berbasis Web Untuk Kafe Kopi Sakura Dengan Metode Prototipe - Muhammad Gabriel Somoal; Nur Chalik Azhar, S.Kom., M.Kom (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2023)
The primary goal of this study is to develop a web-based financial management information system specifically for Sakura Coffee Cafe by using prototype methodologies. Due to manual financial management, the cafe is currently having issues. This results in stress and lower employee motivation in addition to decreasing work efficiency and effectiveness. The creation of an online, user-friendly financial management information system is the aim of this research, which will raise financial management's overall efficacy. This research produces an effective financial management system for Sakura Coffee Cafe by using the prototype method in system design. Proven through User Acceptance Test with black box testing, and a confusion matrix value of 87,8%, which confirmed the suitability of the system as the right solution for users.